Prenatal Opioid Exposure and ADHD Childhood Symptoms: A Meta-Analysis - Ashlyn N. Schwartz; Lucia M. Reyes; Laurie L. Meschke; Kristina W. Kintziger (MDPI AG, 2021)
To systematically investigate the association between prenatal opioid exposure (POE) and attention-deficit hyperactivity disorder (ADHD) symptoms in children 2-18 years old, studies were searched using PubMed, CINAHL, PsycINFO, and Web of Science from January of 1950 to October of 2019. Inclusion criteria were observational studies reporting ADHD symptoms of children with POE compared with non-exposed children or normative data. The study protocol was registered with PROSPERO: CRD42018115967. Two independent reviewers extracted data on hyperactivity/impulsivity, inattention symptoms, ADHD combined subscale symptoms, and sample characteristics. Of 223 articles screened, seven met the inclusion criteria. Data represent 319 children with POE and 1308 non-exposed children from 4.3 to 11.2 mean years from five countries. POE was positively associated with childhood hyperactivity/impulsivity (d = 1.40; 95% CI, 0.49-2.31; p = 0.003), inattention (d = 1.35; 95% CI, 0.69-2.01; p < 0.0001), and combined ADHD symptoms scores (d = 1.27; 95% CI = 0.79-1.75; p < 0.0001). POE was positively associated with ADHD combined symptom scores at preschool (d = 0.83, 95% CI, 0.57, 1.09; p < 0.0001) and school age (d = 1.45, 95% CI, 0.85 to 2.04; p < 0.0001). Results suggest increased risk of ADHD symptoms during school age. Future research is needed to clarify the relationship between biological, social, and environmental risk and ADHD symptoms for children who experienced POE.